2016
DOI: 10.12973/eurasia.2016.1530a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Turkish and Korean Students’ Science and Mathematics Achievement in TIMSS 2011

Abstract: This study makes an important contribution to an expanding body of international comparative studies by exploring factors predicting differences in science and mathematics achievement by students in Turkey and the Republic of Korea on the 2011 TIMSS assessment. While these countries are similar with regards to population size, cultural beliefs about education, and public expenditure on education, students in each country have different levels of achievement in science and mathematics. The current research inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 41 publications
8
35
0
5
Order By: Relevance
“…The educational system should clearly be focused on enhancing students' confidence, and students should be more motivated in order to be more successful. Additionally, the association between parents' highest education level and academic achievement has been found significant in many studies (Berberoğlu, Çelebi, Özdemir, Uysal, & Yayan 2003;Topçu et al, 2016;Wößmann, 2005). This is a general idea, not only for Turkish eighth-grade students, but also for all students in the education system.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The educational system should clearly be focused on enhancing students' confidence, and students should be more motivated in order to be more successful. Additionally, the association between parents' highest education level and academic achievement has been found significant in many studies (Berberoğlu, Çelebi, Özdemir, Uysal, & Yayan 2003;Topçu et al, 2016;Wößmann, 2005). This is a general idea, not only for Turkish eighth-grade students, but also for all students in the education system.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…Higher parental educational levels positively correlate with students' academic achievement. Topçu et al (2016) suggested evening classes or summer institutions for students' lesser educated parents in order to increase their knowledge and awareness. Also, educational resources are another important indicator of success, and students who can reach educational resources easily are generally included in successful groups.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While doing this, a different set of factors regarded as potentially effective on success has been considered. As was pointed out by Topçu, Erbilgin, and Arıkan (2016), finding the significant factors associated with students' success offers significant insights on low success and provides a guidance on which revisions are needed in the current curriculum to enhance success. To this end, a set of factors which can be seen as important causes of crossnational difference in students' science success was handled in this research.…”
Section: Factors Affecting Science Successmentioning
confidence: 99%
“…On the other hand, Students Like Learning (SL), Students Confident (SC) and Students Value (SV) scales are created separately for each specific content. Except SSB, numerous studies have been conducted to investigate the importance of these scales on students' success (Kaya & Rice, 2010;Lai, Ye, & Chang, 2008;Smith, Pasero, & McKenna, 2014;Thomson, 2008;Tsai & Yang, 2015;Topçu, Erbilgin, & Arıkan, 2016). Since SSB scale is newly created, a limited number of studies dealing with its effect have been available (Hu, Leung, & Chen, 2018;Smith et al, 2019).…”
Section: Factors Affecting Science Successmentioning
confidence: 99%